The Effect of Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR) & Loan To Deposit Ratio (LDR) on Return on Assets (ROA) (Case Study: Government-Owned National Banks) - Helmy Assegaff; Wita Juwita Ermawati; Alim Setiawan Slamet (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) in state-owned conventional commercial banks during the 2019–2023 period. The research employs multiple linear regression analysis using SPSS 25. The sample consists of four state-owned conventional commercial banks. The F-test results indicate that NPL, CAR, and LDR simultaneously have a significant effect on ROA, with an F-value of 21.925 and a significance level of 0.000. Partially, only the NPL variable has a significant effect on ROA, as shown by a t-value of -5.312 and a significance level of 0.000. Meanwhile, the CAR and LDR variables do not have a significant effect on ROA, with significance values of 0.318 and 0.961, respectively. Thus, it can be concluded that only NPL significantly affects the bank's profitability as measured by ROA.